The Role Of Agrarian Cultural Values In Building Destination Brand Equity In Jatiluwih Rice Terraces - Pradnyandari, Anak Agung Sagung Devi Suamba; Darmawan, Dwi Putra; Arisena, Gede Mekse Korri (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
This research aims to inspect the role of agrarian cultural values in mediating the influence of destination brand awareness, association, image, quality, and satisfaction on destination brand equity and expand the Jatiluwih Rice Terraces branding by including cultural aspects by considering visitors' points of view regarding destination brand awareness, association, image, quality and satisfaction. This research was using Latent Variable Analysis (Lavaan) to analyze data. The number of samples in this study was determined to be 68 respondents. The data collection technique through interviews with questionnaire tools starts from measuring variables which are carried out by creating indicators to prevent deviations from the main problem. This paper provides empirical insight into how agrarian cultural values are influenced as a mediating variable. This shows that agrarian cultural values are not the reason why visitors visit Jatiluwih Rice Terraces. However, it can be seen that the more satisfied visitors are, the greater their curiosity about the agricultural and cultural values. The study's findings might not broadly apply because of the selected research methodology. As a result, researchers are encouraged to test the suggested theories further. This article contains implications for developing agrarian cultural values, namely by collaborating with the tour guide, and providing provision or training so that the tour guide is able to explain the cultural values of the Jatiluwih Rice Terraces. Apart from that, the management of Jatiluwih Rice Terraces can add in-depth cultural information on the website and flayer which will be given to visitors at the entrance.